Modelo de governança para a rede de incubadoras de empresas do Ceará (RIC) - Germano, Cíntia Vanessa Monteiro (2013)
Business incubators first appeared in Brazil in the 1980s and, according to the literature, have been a solid institution over the past 10 years. They provide subsidies for the preparation of new enterprises and favor the dissemination of an entrepreneurial culture, thereby stimulating the development and growth of new and small businesses. Incubators may be organized into networks which have an executive function. Such networks help accomplish the goals of the incubators by creating a synergy between members for greater overall efficiency and competitiveness. To do so, a network must provide a framework in which a set of connected organizations can carry out long-term cooperative actions aimed at common and/or complementary objectives. Studies have shown that incubator networks can be operationalized using a governance model which reflects the way the objectives of the network should be accomplished. Such models have already been adopted in some incubators, technopoles and incubator networks. The adoption by incubator networks of governance principles can improve the level of transparency and communication between managers and stakeholders and create value for the institution. The objective of this study was to evaluate the level of adherence of the Ceará Network of Business Incubators (RIC) to a theoretical governance model for incubator networks. The purpose of the RIC is to promote integrated development of innovative firms through business incubators, technopoles and incubator programs. This was an exploratory and qualitative single-case study based on the collection of primary data through questionnaires and meetings with the study subjects (the chairman of RIC and the managers of seven of the eight member incubators) between September 2012 and March 2013. The results show that the profile of the member incubators is similar to that observed in a national study by ANPROTEC (2012). This was somewhat surprising since the practice of business incubation was only recently introduced in the state of Ceará. In addition, our results show that, according to the managers of the member incubators, RIC adheres to certain practices of corporate governance, such as equity and corporate responsibility. It may therefore be concluded that, although no structured governance model has yet been formally adopted, RIC adhered partially to the theoretical governance model for incubator networks. However, as an agent of governance, the network can optimize its relationship with voluntary and, especially, involuntary stakeholders (represented in the model by the member incubators, incubated businesses and graduates), thereby raising the level of confidence between the parts and boosting overall competitiveness.